Philosophy Of Language: Pragmatic Presupposition in Motivational Speech Within Discourse and Its Relevance Of Motivation in Teaching Learning Process to Reach Goals - Nistiti, Nurul Ulfa (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2021)
This research was taken from online media in the form of a speech on a YouTube channel called the English Speeches Channel featuring an inspiring woman named Muniba Mazari Baloch. She is a Pakistani artist, model, activist, motivational speaker, singer, social reformer, and television host. Her motivational speech is titled we all are Perfectly Imperfect. This research accompaniment three research questions by analyzing the types of presuppositions contained in Muniba Mazari's speech and determining the type of presupposition in his speech that comes up with the confession discourse function, then knowing how far her confessions influences her audiencess through what he delivers. The research method used in this research is descriptive qualitative by analyzing several utterances in her speech, through two approaches of theory pragmatic presupposition and confessional discourse analysis. The results showed that Muniba Mazari used all types of pragmatic presuppositions (Existential, Factive, Non-Factive, Lexical, Structural, and Counterfactual). Through this type of presupposition, Muniba Mazari also brings out the function of confessional discourse. The function of confessional discourse contained in her speech is a therapeutic, didactic, and interrogatory function. During the research, researchers found the main threat from the combination of these two theories is the strength of Motivational Assertion. The main threat that became the main idea as the direction of Muniba Mazari's speech in motivating her audiences. Then, this main thread also asserts how powerful Muniba Mazari's speech was. In this context, the results bring about optimism, achievable objectives, passion, and confidence. Finally, Muniba Mazari's speech entitled We Are Perfectly Imperfect which contains many moral messages can be said to be a motivational speech. It can be manifested in learning-teaching process. The result of combining these two theories produces the main thread that can be applied by several teachers in motivating their students in the learning-teaching process.